A multi-criteria decision-making (MCDM) approach to determine the synthesizing routes of biomass-based carbon electrode material in supercapacitors. (15th April 2023) - Rahimi, Mohammad; Thanh, Hung Vo; Ebrahimzade, Iman; Abbaspour-Fard, Mohammad Hossein; Rohani, Abbas
Abstract: The selection of desirable synthesis procedures to achieve the idea of physiochemical and capacitive properties of activated carbons (ACs) can be carried out by the multi-criteria decision-making (MCDM) technique. The technique of ordering preference by similarity to an ideal solution (TOPSIS) is a well-known MCDM method with a superior selection of ideal materials. The present work elaborates a framework by establishing the TOPSIS method to obtain ideal synthesizing features, materials, and electrochemical measurements of AC electrode. The 21 multi-alternatives are considered from (i) temperature/heating rate of carbonization, chemical activating/doping, and post-purifying procedures of ACs; and (ii) the ratios of components, electrolytes, and potential window from AC-derived electrodes. 12 creteria are obtained from categories include microstructure properties, heteroatoms content of ACs, and gravimetric capacitance of AC electrodes used in electric double-layer capacitors (EDLCs). TOPSIS proposed scores for activating agent ratio, activation temperature, and heating rate of 0.68, 0.65, and 0.57 on the physiochemical criteria of AC, respectively. Also, the electrolyte concentration, type, and ratio of activating agents were ranked with 1, 082, and 062 scores on electrode capacitance, respectively. Moreover, TOPSIS exemplified two-step hydrothermal-assisted synthesis, artificial doping, and 6M HCl for purifying to achieve ACs with ideal physiochemical and capacitive performance. The MCDM technique proved that it can be applied to select the ideal material and process in AC-electrode fabrications with less time, financial, and environmental costs. Graphical abstract: Image 1 Highlights: MCDM was selected to propose the best fabrication processes for electrochemical criteria. TOPSIS was employed to evaluate the AC synthesizing alternatives and capacitive criteria. Eleven physicochemical sub-criteria were defined based on three main criteria. Ideal values of electrochemical alternatives are exemplified by gravimetric capacitance criteria.